Supercapattery: Technical challenges and future prospects - Ansari M.N.M.; Nordin N.A. (Elsevier, 2023)
This chapter summarizes the overview of supercapatteries and challenges in terms of their electrode materials, electrolytes, and electrochemical performance evaluation. Moreover, the prospects of supercapatteries that carry both the merits of supercapacitor and batteries are illustrated. Subsequently, this chapter will discuss the prospects of supercapattery with suitable examples. Finally, it also explores the market potential of supercapattery that can provide a sustainable solution for energy storage applications. 2021 Elsevier Inc.